Energilagring i metaller - Ahlberger, Vidar; Jonsson, Linnea; Petrén, Albin (My University, 2017)
There is a need for a major and rapid transition to renewable energy. Because of the low energy density and intermittent nature of renewable energy sources, there will likely also need to be a rapid development of energy storage methods. In this project thermochemical energy storage, TCS, has been studied with the intention to improve this way of storing energy. For a working TCS system, research is needed in three different areas; development of the reactor system, process integration and selection of storage materials. In this project the focus has been on the latter part, the selection of materials, which is the key for a successful implementation. The project includes a review of previous research done in the area with emphasis on what systems have been studied experimentally. A thermodynamic evaluation was also performed on different oxide systems. Finally an experimental investigation was conducted, including selection and synthesis of the metal oxides, reactivity testing and kinetic modelling. The summary of the literature study showed that the research mostly has been centered around manganese oxides. This is because the metal is cheap, easily accessible, persevering and it has good thermodynamic characteristics. Other metal oxides mixed with manganese oxide have also been in consideration. In this study all the experiments have been done on mixed oxides with manganese included in the matrix. The selected materials were: Mn70Fe30 (70% Mn3O4 and 30% Fe2O3), Mn48Mg51 (48% Mn3O4 and 51% MgO), Mn94Si06 (94% Mn3O4 and 6% SiO2) and Mn79Fe20Cu01 (79% Mn3O4, 20% Fe2O3 and 1% CuO). The experimental part consisted of making one of the materials (Mn79Fe20Cu01) with solid state synthesis. Three compounds were spray-dried, two of these were selected from previous studies. Characterization of the phases of the compounds was done with x-ray powder diffraction and temperature cycling with thermogravimetric analysis. The temperature cycling was made in the temperature range 600-1000 C in air. From the x-ray diffraction is was not possible to determine if the synthesis had been successfull for the manufactured compound but it showed good results in the temperature cycling. Mn70Fe30 also showed good results in the cycling while the other two proved to be less reactive. A kinectic evaluation was also conducted on Mn70Fe30, where the activation energy, frequency factor and reaction model for oxidation and reduction was studied. An activation energy of 124 kJ/mol was calculated for the oxidation and 294 kJ/mol for the reduction. From the study performed it is clear that all materials worked relatively well, i.e. were oxidized and reduced at the investigated temperature interval. Still, in order to judge the applicability it is necessary to conduct further tests.
Keywords: Energiteknik; Hållbar utveckling; Energi; Energy Engineering; Sustainable Development; Energy